P202 Accuracy of blood-PCR for diagnosing CMV Colitis in patients with Inflammatory Bowel Disease. (30th January 2023) - Serra-Ruiz, X; Herrera-de Guise, C; Esperalba, J; Mayorga Ayala, L; Céspedes Martínez, E; Robles Alonso, V; Casellas, F; Pérez Martínez, Z; Oller, E; Borruel Sainz, N
Abstract: Background: Current guidelines in inflammatory bowel disease (IBD) advocate for endoscopic biopsies to confirm cytomegalovirus (CMV) colitis by means of immunohistochemistry (IHC) or tissue polymerase chain reaction (tPCR). Clinical usefulness of whole-blood PCR (bPCR) remains controversial. Our aim was to asses diagnostic accuracy of bPCR to predict CMV colitis. Methods: We extracted data from all patients between 2017 and 2022 with ulcerative colitis (UC), Crohn's disease (CD) or unclassified colitis presenting with a moderate-to-severe flare of IBD, and who were tested for CMV infection with both IHC and bPCR at the same time. IHC was considered reference standard and was used to evaluate diagnostic accuracy of bPCR. Results: 89 patients were included, of which 44 (49, 4%) were women, and median age was 49 years (Figure 1). 48 (50, 6%) had UC, 16 (19, 1%) had CD, and 25 (29, 2%) had unclassified colitis. 46 (51, 7%) were receiving any IBD treatment by the time of enrolment, of which 34 (67, 4%) were on corticosteroids. Among patients in the CMV colitis group we found a higher proportion of leucocyte counts in the normal concentration range (p=0, 035) and higher endoscopic activity using the Mayo endoscopic score in CU (p=0, 027). Of the study subjects, 25 (28, 2%) had CMV colitis; and bPCR was positive in 23 (25, 8%). Diagnostic accuracy of bPCR was 75, 3%, being sensitivity and specificity 52% and 84, 4%, respectively. The positive predictive value and negative predictive value were 56, 5% and 81, 8%. Numerically, patients in the CMV colitis group showed higher concentrations of CMV DNA PCR without reaching statistical significance (6416, 2 copies/mL vs. 2256 copies/mL, p=0, 295). The area under the receiver operating characteristic curve value was 0, 646 (p=0, 239). When setting a threshold of above 1336 copies/mL, sensitivity and specificity values were 40% and 92, 2%, respectively, and the positive likelihood ratio (LR+) was 5, 13 (Figure 2). Conclusion: Although bPCR showed high specificity for diagnosing CMV colitis, the sensitivity values were low. In agreement with current guidelines, blood-based tests should not replace IHC or tPCR for detecting CMV reactivation in IBD. A threshold of above 1336 copies/mL showed a moderately high LR+, thus it should prompt consideration of early antiviral treatment.